2010
DOI: 10.4103/0378-6323.69078
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis in the pediatric population: A study from North India

Abstract: In the present study, clinical morphology or KOH findings were not found to be clearly or exclusively predictive of the species involved. There was a fair degree of overlap in the clinical or microscopic patterns produced by the fungal species. Mixed patterns were observed both on clinical examination as well as on KOH examination. However, none of the specimens grew more than one fungal species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 11 publications
(27 reference statements)
10
49
4
Order By: Relevance
“…Grover et al (2010) also reported similar type of findings. 14 Tinea capitis rarely occur in normal healthy adults. This may be due to increased fungistatic triglyceride content of sebum in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Grover et al (2010) also reported similar type of findings. 14 Tinea capitis rarely occur in normal healthy adults. This may be due to increased fungistatic triglyceride content of sebum in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The etiologic agents of dermatophytosis are classified into three genera based primarily on differences in microscopic morphology and modes of sporulation as Epidermophyton, Mirosporum and Trichophyton 16 . Tinea capitis is a highly contagious common dematophytic infection seen predominantly in children caused predominantly by Trichophyton or Microsporum species 17 . Clinical presentation of disease revealed that scaly type to be the commonest (60%) followed by black dot type (39%) and kerion type was the least (1%).These findings in this study were similar to the study of Gargoom et al 18 and Jha et al 19 .…”
Section: Discussionmentioning
confidence: 99%
“…TC is usually not seen after puberty, since seborrhea prevents development of TC (1). In a study from Iran, the prevalence of cutaneous mycosis was studied in nonmedical staff of the Medical Center of Ahvaz University Medical School.…”
Section: Resultsmentioning
confidence: 99%
“…TC is caused by anthropophilic, geophilic, and zoophilic subtypes of Trichophyton and Microsporum dermatophytes (1)(2)(3)(4). TC has 3 clinical forms: TC superficial (noninflammatory), TC profunda (inflammatory), and TC favosa (favus).…”
Section: Introductionmentioning
confidence: 99%